Chapter C4 Restricted Verbal Interaction in Court - Durant, Alan (Taylor & Francis, 2016)
Language plays an essential role both in creating law and in governing its implementation. Providing an accessible and comprehensive introduction to this subject, Language and Law:describes the different registers and genres that make up spoken and written legal language and how they develop over time; analyses real-life examples drawn from court cases from different parts of the world, illustrating the varieties of English used in the courtroom by speakers occupying different roles; addresses the challenges presented to our notions of law and regulation by online communication; discusses the complex role of translation in bilingual and multilingual jurisdictions, including Hong Kong and Canada; and provides readings from key scholars in the discipline, including Lawrence Solan, Peter Goodrich, Marianne Constable, David Mellinkoff, and Chris Heffer. With a wide range of activities throughout, this accessible textbook is essential reading for anyone studying language and law or forensic linguistics.